HADOOP Ecosystem Analytics and Big Data for Advanced Computing Platforms - Asmita Singh, Sunita Choudhary, Manju Kumari (International Journal of Advanced Science and Technology, 2020)
As information is being increased each second and there is a more noteworthy prerequisite to deal with and oversee such a tremendous measure of information. This need obliges discover systems to overlook what we call is Big Data. We accumulate information from various sources like association, sensor, camera, web and so forth. With the quick increment of unconstructed information, it has turned out to be hard to process with customary apparatuses of database for the executives. That is the reason the term Big Data has been coined. To dissect and examine such gigantic measure of various kinds of information, there is a necessity of enormous information examination. It handles heterogeneity, scale, practicality and multifaceted nature of information. There are two fundamental classes of proficiently processing this huge measure of unstructured information Hadoop and Non-Hadoop. By utilizing these classifications Big Data involves the accompanying qualities which are Volume, Velocity and Complexity of information. This Big information advances settle on quick choices. Each association is currently sending towards it. It is as yet a rising subject that accumulates a great deal of new innovations, and need an opportunity to develop. In any case, then again, it has a genuine market opportunity. This paper discusses Hadoop and its Ecosystem, Hadoop highlights and the job of Big Data in all these technologies. Keywords: - Hadoop Ecosystem, Map Reduce,HDFS, HBase, Hive, Yarn.